Advanced And Lightweight Concrete: An Analysis Of Characteristics And Utilizations In Sustainable Construction - Yuhuan, Zhao; Al-odaini, Aiman Al-odaini (Journal of Neonatal Surgery, 2025)
Using citation-context and the paper's content model, the researcher summarize sustainable building developments, including research into the properties and uses of high-performance and lightweight concrete. Scientific summaries generated from citations have a poor track record of success because they lack crucial context. Our evaluation dataset is from the construction business, but our methodologies are generally applicable, therefore they may be used in other domains as well. Sustainable construction innovations are at a crossroads; they need to promote global prosperity while reducing their environmental footprint. The building sector is now at a crossroads; it can either help the globe prosper or harm the environment. If this problem persists, using high-performance, lightweight concrete might be the answer. This material greatly decreases the carbon impact while also improving the sustainability of building operations. The possible repercussions of the pressing need for greener alternatives to conventional building practices are the subject of this investigation. The benefits of high-performance plus lightweight concrete are emphasized, such as its decreased carbon emissions, enhanced thermal insulation, less weight, and more adaptability. These cutting-edge materials have already shown their worth in famous projects like Milan's Bosco Vertical and Amsterdam's 3D-printed concrete bridge, which both promote environmentally friendly building methods. The study concluded that in order for the construction sector to completely adopt this technology, it must engage in research, get regulatory backing, educate itself, and include stakeholders. A coexistence of development with environmental care may be possible as a result of this research. The environment is greatly impacted by conventional building procedures